Bagaimana Media Memberitakan Pandemi: Analisis Isi Berita Mengenai COVID-19 di detik.com dan kompas.com - Aribah, Ghina; Anshari, Dien (UI Scholars Hub, 2021)
Introduction. During the pandemic COVID-19, online news is one of the most accessible channels to disseminate information about the current situation and prevent and mitigate the disease. Objective to get the portrayals of risk communication in news articles about the COVID-19 pandemic Methods. Used content analysis method with descriptive quantitative approach. Data came from selecting news articles published by detik.com and kompas.com in March and April 2020 using a stratified proportional random sampling technique. Results. There were limited news articles that provide epidemiology information, disease characteristics, how to mitigate the disease, the non-health effects of COVID-19, and criticism of the government’s policy. Almost half of the articles from both media shared information about prevention. In terms of message type, most of the articles used threat messages. Both media also mostly cited institutions as the source of information. Both media differ in depicting the evidence, whereas detik.com mostly used narrative forms, while kompas.com more frequently used the combination of numbers, statistical data, and narrative structures. Conclusion. News on detik.com and kompas.com is not entirely in line with the rules in risk communication. Online news media should incorporate efficacy messages into their news articles during this pandemic situation.